Analisis Implementasi FIFO–FEFO dalam Meningkatkan Efektivitas Inventory Control pada Operasional Logistik Retail: Studi Kasus KPDK Mart Kementerian Koperasi Republik Indonesia - Aisyah Indarsari; Natasya Tita Zalianty; Nadhifah Fakhirah (Jurnal Logic: Logistics & Supply Chain Center, 2026)
The effectiveness of inventory control is an important factor in supporting retail logistics operations. However, inventory management still faces various obstacles, such as storage systems that are not yet standardized, inconsistent implementation of stock rotation, and the discovery of expired products. This research aims to analyze the implementation of rack labeling, First In First Out (FIFO) and First Expired First Out (FEFO) methods in increasing the effectiveness of inventory control at KPDK Mart, Ministry of Cooperatives of the Republic of Indonesia. The research uses a descriptive qualitative approach with a case study method. Data was obtained through field observations, documentation, and discussions with managers, then analyzed using data reduction, data presentation, and drawing conclusions. The research results show that the rack labeling system increases inventory visibility through more structured identification of storage locations, thereby supporting the process of searching, placing and monitoring goods. Meanwhile, evaluation of the implementation of FIFO and FEFO shows that stock rotation and shelf life monitoring have not been running consistently, as indicated by the discovery of expired products in the display area. This research concludes that the integration of rack labeling, FIFO, and FEFO contributes to increasing the effectiveness of inventory control through increasing storage regularity, controlling stock rotation, and reducing the risk of expired products. These findings can be a reference for retail managers, especially retail cooperatives and small and medium scale retail businesses, in improving the quality of inventory management.